The geoelectric approach to analyzing the profile of post-mining nickel laterite deposits in the Motui District, North Konawe Regency, Indonesia. Issue 1 (1st January 2023) - Mustafa, H; Maulana, A; Irfan, U R; Tonggiroh, A
Abstract: The profile of laterite nickel deposits following mining operations can be determined using a geoelectric method, which is crucial information for exploration as well as sustainability. The purpose of this research is to ascertain the physical properties and thickness profile of laterite nickel deposits in the subsurface following mining. The geoelectric method used is resistivity to map variations in the apparent resistivity values of rocks. This value reflects the different types of rock layers in the subsurface. Through the use of two electrodes, an electric current was introduced into the earth, and the potential difference that resulted from this injection was then measured. Based on the configuration of the electrodes utilized, the apparent resistivity value can be determined. The profile of laterite nickel deposits in the Motui post-mining area includes three layers, red limonite, yellow limonite, and bedrock, with resistivity values ranging from 17.0 to 1572 Ωm. The resistivity of the red limonite layer ranges from 17.0 to 1572 Ωm, and its depth is 0 to 10 meters. The yellow limonite layer is between 10 and 20 meters thick and has a resistivity range of 17.0 to 31.8 m. The resistivity of bedrock, on the other hand, ranges from 84.2 to 1572 Ωm at depths between 20 and 70 meters.